TRAFFIC CALMING (Perner's Contacts, 2009)
The paper deals with the traffic calming in the urban space. Traffic calming shares the goal of reducing vehicle speeds, improving safety, and enhancing quality of life. Traffic calming starts to occur in many Czech towns. There is given account to traffic calming in Trnovska Street in Pardubice.